FORMS OF PUBLIC ADMINISTRATION OF TRAINING WITH HIGHER MILITARY EDUCATION FOR THE ARMED FORCES OF UKRAINE - Ziborieva, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The purpose of this article is to define the concept and types of forms of public administration for training personnel with higher military education for the Armed Forces of Ukraine. The article analyzes theoretical approaches to the problem of the essence of the forms of public administration. The work highlights the most important features of these forms. The definition of the forms of public administration of personnel training with higher military education for the Armed Forces of Ukraine has been formulated: these are ways of external expression of the achievement of the goals set for the subjects of public administration in this area, carried out by legal and extra-legal (organizational) methods. Taking into account the principle of differentiation by nature and legal nature, it is proposed to divide such forms into four main types: a) rulemaking activities aimed at establishing and specifying the rights, duties and responsibilities of the subjects of the educational process in higher military educational institutions and military educational units of higher educational institutions; b) the publication of executive and administrative and individual legal acts; c) implementation of legally significant actions with the publication of an official document; d) the implementation of interim actions necessary to support the training of personnel with higher military education for the Armed Forces of Ukraine (this includes a wide range of activities related to organizational, managerial, informational, material and technical, personnel, psychological and other types of training for officer personnel). The article substantiates that the forms of public administration of training personnel with higher military education for the Armed Forces of Ukraine are an integral part of the conceptual apparatus of public administration in the security and defense sector. The ontological nature of the studied forms of public administration is due to the need for the practical implementation of legal prescriptions at the legal and individual level to achieve the goals of legal regulation (ensuring the defense capability of the state by training the required number of officers who have the necessary knowledge, skills, skills and personal qualities).
Keywords: public administration, forms of public administration, personnel training, the Armed Forces of Ukraine, higher military education, legal forms, extra-legal forms, legal regulation